2019
DOI: 10.35940/ijeat.f1111.0986s319
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Management’s Commitment with Job Satisfaction According to Shari’ah-Based QMS (MS1900:2014) at Malaysian Higher Education Institution

Abstract: Management’s commitment in an organisation plays an important role in ensuring the application of effective quality management system (QMS). This article explores the relationship between management’s commitment of an organisation that implements Shari’ah-based Quality Management System (MS1900:2014) with job satisfaction at Malaysian Higher Education Institution (HEI). The methodology of this study employed a qualitative design via a semi-structured interview conducted on selected respondents. The respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many scholars have investigated topics on quality management activities such as Total Quality Management (TQM), Quality Control and Quality Assurance (i.e, Easton & Jarrell, 1998;Kannan & Tan, 2005;Powell, 1995;Robin & Kehoe, 1994;Samson & Terziovski, 1999;Chiarini, 2020;Shahibah, Hariadi & Baridwan, 2020;van Kemenade, 2021). Nevertheless, there are limited studies which covers this topic from the Islamic perspective (i.e, Sarion, 2015;Mohamed, 2019;Mokhtar, 2019;Ishak, 2019;Mohamed, 2021). This research will investigate on the MS1900:2014, a Shariah-based Quality Management System which is established in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have investigated topics on quality management activities such as Total Quality Management (TQM), Quality Control and Quality Assurance (i.e, Easton & Jarrell, 1998;Kannan & Tan, 2005;Powell, 1995;Robin & Kehoe, 1994;Samson & Terziovski, 1999;Chiarini, 2020;Shahibah, Hariadi & Baridwan, 2020;van Kemenade, 2021). Nevertheless, there are limited studies which covers this topic from the Islamic perspective (i.e, Sarion, 2015;Mohamed, 2019;Mokhtar, 2019;Ishak, 2019;Mohamed, 2021). This research will investigate on the MS1900:2014, a Shariah-based Quality Management System which is established in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…They found that academic freedom, individualism and collegiality have negative effects on ISO 9001, while professionalism had influenced ISO 9001 both positively and negatively. Meanwhile, Mohamed et al (2019) explored the relationship between management's commitment and employee satisfaction of an ISO-certified HEI. The study revealed that management's commitment of the ISO-certified HEI has apparently influenced job satisfaction among employees.…”
Section: Introductionmentioning
confidence: 99%